Count Ernesto Patrizio de Castiglione and his companies: the italian presence in shadow theatre in 19th-century Brazil. (Móin-Móin Magazine - Studies in the Art of Puppetry, 2025)
This text aims to examine the activities of Count Ernesto Patrizio and his companies in 19th-century Brazil, highlighting his significant contribution to the dissemination of early shadow theatre practices in the country. Drawing on primary sources such as newspapers and performance programs, the study traces the artist's four visits to Brazil between 1875 and 1887, emphasizing his use of shadows, magic lanterns, illusionism, and other theatrical devices. By contextualizing these practices within the theatrical landscape of the time, the article seeks not only to map Patrizio’s journey through Brazil but also to shed light on the early development of shadow theatre in the country, contributing to the reconstruction of a largely unexplored chapter in its history.
Keywords: Shadow Theatre; Count Ernesto Patrizio; 19th-century Brazil